FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PASIEN GANGGUAN JIWA MELAKUKAN PENGOBATAN RUTIN KE PUSKESMAS SIDODADI KECAMATAN KOTA KISARAN BARAT KABUPATEN ASAHAN TAHUN 2018 - Elisabeth Dame Manalu; Nina Dwi Yanti Siagian (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2019)
Mental health is a state where one is free from mental disorders and has a positive attitude to describe maturity and personality. Based on preliminary studies at Sidodadi Public Health Center, patients suffering from anxiety as many as 26 people and patients suffering from depression as many as 38 people. The purpose of this study is to determine the factors that influence the patient's compliance with mental disorders doing routine treatment to Sidodadi Health Center District West Kisaran City Asahan Region 2018, with the type of quantitative writing that is analytic. The population in this writing is the entire head of the family of patients who have mental disorders anxiety and depression that is as many as 64 people. The sampling technique used is total sampling. Data were collected by interviews using the questionnaire. Data analysis was done univariate and bivariate with the Pearson correlation test. The findings of the research showed that there was significant influence between family attitudes, family support, the distance of Health Center, support of health workers. The most dominant variable that influenced the patient's compliance with mental disorder to do routine treatment is the support of health manpower 5.8 times. Head of Health Center to encourage health workers to continue to visit the family home of mental disorders so that they can help the healing process or care for people with mental disorders.